2001
DOI: 10.1016/s0008-6363(00)00242-x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of ventricular and atrial myocytes from pacing-induced canine heart failure

Abstract: We have identified components of the signalling pathways along which apoptosis proceeds following the induction of heart failure in dogs. Apoptosis was also detected in the atria raising the possibility that, like human dilated cardiomyopathy, the molecular changes are global.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…This is followed by myocardial remodeling and development of overt heart failure (22). Heinke et al found that the expression of both caspase-2 and -3 elevates in the left ventricle of dogs with heart failure and over-expression of caspase-2 results in apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by myocardial remodeling and development of overt heart failure (22). Heinke et al found that the expression of both caspase-2 and -3 elevates in the left ventricle of dogs with heart failure and over-expression of caspase-2 results in apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Heinke et al measured the expression of apoptotic molecules (Fas and Fas ligand) in cardiac tissue from the atria and ventricles of dogs, which had undergone rapid ventricular pacing for a period of 4 weeks. They found a significantly elevated expression of apoptotic inducers compared to samples from control, non-paced hearts [13]. Dr. Aime-Sempe examined human right atrial tissue samples from patients who had undergone cardiac surgery (mainly for mitral valve disease) for the presence of apoptosis associated with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic cardiomyocytes have also been detected in ADR induced DCM rats, rapid pacing-induced DCM dogs and biopsy samples from DCM patients [33][34][35]. An apoptosis related protein, Fas, was reported to play an important role in inducing cardiomyocyte apoptosis in DCM.…”
Section: Discussionmentioning
confidence: 99%